2014
DOI: 10.1007/s00167-014-3233-9
|View full text |Cite
|
Sign up to set email alerts
|

Computer-assisted surgery improves rotational positioning of the femoral component but not the tibial component in total knee arthroplasty

Abstract: but no differences were found when comparing CAS and standard instrumentation. Conclusion CAS improves frontal alignment in TKA, especially in the presence of preoperative deformities. In the femoral component, navigation most closely replicated the ideal 3° external rotation of the femoral component, but tibial rotation did not differ when comparing CAS to standard instrumentation. Level of evidence II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 38 publications
1
39
0
Order By: Relevance
“…Recovery of the correct coronal limb alignment and femoral prosthesis rotation alignment are essential for good postoperative function. Poor coronary limb alignment can lead to residual deformities and accelerated wear of the prosthesis, while poor rotational alignment of the femoral prosthesis can cause imbalance of the flexion gap and poor patellar tracking, which will eventually affect knee function [1,12]. In this study we found that although there was no significant difference in the mFTA, the femoral prothesis was more internally rotated in group B patients.…”
Section: Discussionmentioning
confidence: 63%
“…Recovery of the correct coronal limb alignment and femoral prosthesis rotation alignment are essential for good postoperative function. Poor coronary limb alignment can lead to residual deformities and accelerated wear of the prosthesis, while poor rotational alignment of the femoral prosthesis can cause imbalance of the flexion gap and poor patellar tracking, which will eventually affect knee function [1,12]. In this study we found that although there was no significant difference in the mFTA, the femoral prothesis was more internally rotated in group B patients.…”
Section: Discussionmentioning
confidence: 63%
“…Previous studies have investigated and compared the accuracy of tibial cuts achieved with various alignment techniques, including extramedullary guides, computer-assisted navigation, patient-specific jigs, and hand-held surgical navigation. [3456] Chiu et al . [7] reported 59 tibial components (78.7%) that had a tibial cut within 3° of perpendicular to the mechanical axis when using an extramedullary guide.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, many studies have been reported using computer-assisted navigation systems and patient-specific cutting guides to decrease the number of alignment outliers. [345] However, owing to longer procedure times, increased cost, and highly sensitive instruments, most surgeons still choose conventional mechanical alignment guides when performing TKA. These conventional alignment devices can result in unacceptable intraoperative alignment distortions in clinical practice, due to difficulty in accurately identifying the landmarks around the ankle, tibial torsion, abnormal tibial bowing, and ankle joint deformities.…”
Section: Introductionmentioning
confidence: 99%
“…Patients were randomly assigned to each group by means of a random number table. The study methodology of our cases has already been published in a previous paper (19). The angulation obtained was taken to be the mean of the values recorded by the two observers.…”
Section: Methodsmentioning
confidence: 99%
“…The introduction of computer-assisted surgery (CAS) has improved TKR positioning in the frontal axis, avoiding outliers, and has demonstrated its usefulness particularly in major varus-valgus deformities (17,18). However, it has not been demonstrated that CAS improves tibial tray placement in the transverse axis (19).…”
Section: Introductionmentioning
confidence: 99%